TRANSMISI SINYAL ECG (ELECTROCARDIOGRAPH) MENGGUNAKAN MEDIA WIRELESS ZIGBEE DENGAN TOPOLOGI MESH - Harianto, Gaguk; Jusak, Jusak; Puspasari, Ira (Journal of Control and Network Systems (JCONES), 2017)
Heart disease can be experienced by Anybody and sometimes can not be detected, and therefore need to examination conducted by a specialist to prevent heart disease. Electrocardiograph (ECG) is a signal which is formed as a result of the electrical activity of the heart muscle that is taken by placing the electrodes. Electrocardiograph produced can indicate the frequency, rhythm, axis, mark realization mark hypertrophy (enlargement), and signs of ischemic on heart, it would be very helpful for the physician to be able to determine the cardiac condition of the patient so that it can be taken medical early.In this study, cardiac auscultation signal transmission through the transmission of wireless with mesh topology on wireless sensor networks built. Quality of service is used in this research included the probability of loss, delay of data received and the throughput number of cardiac auscultation signal that transmitted.Based on the result of research, the results of cardiac auscultation signal transmission using point to point and use a mesh topology with baudrate 115200 shows that the position and number of nodes affect the transmission of data that set by serial communication, thus directly affects the amount of packet loss, delay and throughput data.